Spontaneous Rupture of the Liver Seen at Autopsy: A Case Report of a Rare Cause of Death in Custody and Literature Review (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
Death in custody is a death of a person in the custody of the police or other authorities  or while in prison. When the causes are studied, they are usually from natural causes  with the heart diseases constituting the majority of cases. We present a case of death in  custody from spontaneous liver rupture, a rare condition with very few cases reported  in literature. We are not aware of any reported case of death in custody secondary  to spontaneous liver rupture. High index of suspicion is required for early diagnosis  of spontaneous liver rupture and should be considered as a possible cause of death  in custody. Adequate medical history of the detainee is important and crucial as  they can detect fatal condition and the prison staff must act promptly to address any  medical concerns of the inmates.
Keywords: Spontaneous liver rupture; death in custody